The Relationship Between Lower Back Pain and Functional Activity in Pregnant Women in The 3rd Trimester at The Paguyaman Community Health Center, Gorontalo Regency - Susanti Bioto; Anik Sri Purwanti; Rifzul Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Lower back pain is a common complaint often experienced by pregnant women, especially in the third trimester (TM 3). This condition can affect the functional activities of pregnant women, such as the ability to walk, stand, and perform daily activities. This study aims to determine the relationship between lower back pain and its effect on functional activities in TM 3 pregnant women at the Paguyaman Health Center, Gorontalo Regency. This study aims to identify a significant relationship between the level of lower back pain and disorders in the functional activities of TM 3 pregnant women at the Paguyaman Health Center. This study used an analytical design with a cross-sectional approach. The sample used was 30 pregnant women in the third trimester who experienced lower back pain. Data were collected through a questionnaire to measure the level of lower back pain and its effect on functional activities. Data analysis was carried out using the chi-square test, and the p-value obtained was 0.000. The results of the study showed that there was a very significant relationship between lower back pain and functional activity disorders in pregnant women in the 3rd trimester, with a p-value = 0.000 (<0.05), indicating a strong influence between the two. Lower back pain in pregnant women in the 3rd trimester has a significant effect on functional activity disorders in mothers. This indicates the need for more attention to the treatment of lower back pain to improve the quality of life and mobility of pregnant women. It is recommended for medical personnel to provide education on how to manage lower back pain and techniques that can help pregnant women reduce pain and improve the quality of their functional activities. In addition, pregnant women should be given information about safe physical exercise to help reduce pain and improve mobility.